APPLICATION OF TEAMS GAMES TOURNAMENT (TGT) LEARNING MODEL IN JURISPRUDENCE LESSON TO INCREASE LEARNING INTEREST OF CLASS X STUDENTS OF MADRASAH ALIYAH NEGERI (MAN) 2 BOGOR CITY - Aden Ardiansyah; Gunawan Ikhtiono; Salati Asmahasanah (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to examine the application of the Teams Games Tournament (TGT) learning model in the subject of Fiqh in class X-10 at Madrasah Aliyah Negeri 2 Kota Bogor, as well as to determine the extent of improvement in students' interest in learning the subject after the implementation of the TGT learning model. The type of research used is Classroom Action Research (CAR), conducted in two cycles, with a total of 31 students as subjects. The data collection methods in this study included observation to monitor teacher and student activities, interviews with Fiqh teachers regarding the implementation of the TGT learning model, and the distribution of questionnaires to measure students' interest in learning Fiqh through the TGT approach. The results of this study show a significant increase in teacher and student activities, as well as in students' interest in learning. Teacher activity in cycle I scored 84, which is classified as “good,” and increased to 91 in cycle II, classified as “very good.” Meanwhile, student activity also increased, from 77 in cycle I to 85 in cycle II. Similarly, student learning interest, which was initially at 71 in cycle I, increased to 82 in cycle II.